Integrasi Teori-Teori Belajar dalam Pembelajaran untuk Mencapai Tujuan Holistik Pendidikan Agama Islam - Andi Abd. Muis; Rahayu Binti Kasper; Sopian Atjo; Arjun Arjun; Ragil Nugaraha; Hartono Hartono; Nur Hiqma; A. Alya Indriani; Fitriani Fitriani; Imba Lalunggaeng (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Islamic Religious Education (PAI) has a holistic goal, namely to shape individuals who are faithful, have noble character, are knowledgeable, and behave in accordance with Islamic teachings. To achieve this goal, the integration of modern learning theories into teaching practices is necessary. This literature review article aims to analyze various learning theories including behaviorist, cognitive, constructivist, humanistic, and social in the context of Islamic Religious Education (PAI) learning in schools. This approach is used to identify the relevance between psychological principles of learning and the comprehensive spiritual values ​​of Islam. This study uses a literature review method, reviewing various scientific sources such as journals, books, and research reports from 2015–2025. The results indicate that the integration of learning theories can enrich the Islamic Religious Education (PAI) learning process by balancing cognitive, affective, and psychomotor aspects. Behaviorist theory supports the formation of worship habits through positive reinforcement, cognitive theory fosters the development of understanding of religious concepts, constructivist theory emphasizes meaningful experiences in understanding Islamic values, humanistic theory fosters spiritual self-awareness, and social theory emphasizes the importance of teacher role models. Thus, Islamic Religious Education (PAI) learning integrated with learning theories can create a holistic, humanistic, and contextual Islamic education that meets the demands of the 21st century.